Biaxial bending of columns with unsymmetrical T sections (working stress design by computers) - Tunca, Tamer. (Thesis (M.S.)- Robert College. Institute for Graduate Studies in Science and Engineering, 1969., 1969)
A numerical method of working stress design of reinforced concrete columns with unsymmetrical T-shaped sections subjected to biaxial bending and axial force is presented. The design procedure, modified on the basis of Turkish Building Code requirements, is similar to Rüdinger's and Chu's iterative solution methods in which the stress at any point is found from a general formula for unsymmetrical bending of unsyrunetrical sections. The formulation derived for T-sections is readily applicable to L-shaped as well as to rectangular sections. The tileory includes the cases in which the eccentricities exceed the cracking limit of the section. A computer program is given and one complete numeric example is included.
Keywords: Columns, Concrete.; Reinforced concrete.